2022
DOI: 10.3390/ijms231810205
|View full text |Cite
|
Sign up to set email alerts
|

Juniperus sabina L. as a Source of Podophyllotoxins: Extraction Optimization and Anticholinesterase Activities

Abstract: Juniperus sabina L. (J. sabina) has been an important plant in traditional medicine since ancient times. Its needles are rich in podophyllotoxin, a precursor compound to anti-tumor drugs. However, no systematic research has been done on J. sabina as a source of podophyllotoxins or their biological action. Hence, extracts of podophyllotoxin and deoxypodophyllotoxin were the main optimization targets using the Box–Behnken design (BBD) and response surface methodology (RSM). The total phenol content and antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
5
10
0
Order By: Relevance
“…As stated in Table 3 , the relative standard deviations (RSDs) of TPC and TFC showed that the predicted values for all groups were very similar to the experimental results. This result is also supported by a prior report [ 38 ]. The suitability of the response surface methodology model for quantitative predictions was verified by a satisfactory agreement between the predicted and measured values.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As stated in Table 3 , the relative standard deviations (RSDs) of TPC and TFC showed that the predicted values for all groups were very similar to the experimental results. This result is also supported by a prior report [ 38 ]. The suitability of the response surface methodology model for quantitative predictions was verified by a satisfactory agreement between the predicted and measured values.…”
Section: Resultssupporting
confidence: 92%
“…To quantify the antioxidant activities of different extracts/compounds, the concentration of the samples required to scavenge 50% of radicals (IC 50 ) was measured. A smaller IC 50 value indicates an increase in free-radical scavenging ability [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study the CV values range from 0.9981 to 3.44. The modified R 2 (R 2 ≥ 0.80) was well within acceptable limits in this study, showing that the experimental data fits second-order polynomial equations satisfactorily [ 29 ]. To demonstrate the interactions between the independent variables, 3D surfaces and contour plots were constructed using multiple linear regression equations.…”
Section: Resultssupporting
confidence: 60%
“…It was reported that a bulky at C-4 could enhance their cytotoxic activities [137]. Some researches indicated that replacing the saccharide chain with a non-saccharide moi- It was reported that the alkoxy-substituted benzene ring was replaced by a pyrazole moiety (105)(106)(107)(108)(109)(110). The antiproliferative properties of these heterocyclic compounds were comparable with the currently used anticancer drug etoposide [136].…”
Section: Ring Cmentioning
confidence: 97%
“…Introducing a hydroxyl group into ring B (104) could remarkably improve the TOPO-II inhibitory activity of epipodophyllotoxin[3]. It was reported that the alkoxy-substituted benzene ring was replaced by a pyrazole moiety(105)(106)(107)(108)(109)(110). The antiproliferative properties of these heterocyclic compounds were comparable with the currently used anticancer drug etoposide[136].…”
mentioning
confidence: 99%